2016
DOI: 10.13075/mp.5893.00440
|View full text |Cite
|
Sign up to set email alerts
|

Work experience and seniority in health care vs. medical students’ knowledge of selected hand hygiene procedures

Abstract: StreszczenieWstęp: Higiena rąk jest podstawowym i najważniejszym elementem profilaktyki zakażeń. Celem prezentowanego badania była analiza wiedzy o higienie rąk wśród studentów wybranych kierunków medycznych Collegium Medicum Uniwersytetu Jagiellońskiego w powiązaniu z ich doświadczeniem klinicznym i szkoleniami dotyczącymi zasad profilaktyki zakażeń oraz analiza oceny przez studentów zachowań personelu medycznego w zakresie przestrzegania higieny rąk. Materiał i metody: Badanie przeprowadzono między październ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
1
15
1
1
Order By: Relevance
“…This group encompasses factors, which may cause disease in people, may be dangerous for workers, but their spread in the human population is unlikely and they may generally be defeated with efficient prophylaxis and treatment. Considering the study results -by Garus-Pakowska cited above -on compliance with hand hygiene of medical staff in dealing with patients, and another one taking into account the correct use of protective gloves (personal protective equipment) [6][7][8], or other authors [20,21] it may be stated that hospital staff often disregard the procedures aimed at protecting against harmful biological agents. Consequently, the hospital environment is not a safe work environment, and in particular it is not a microbiologically safe environment for patients.…”
Section: Discussionmentioning
confidence: 99%
“…This group encompasses factors, which may cause disease in people, may be dangerous for workers, but their spread in the human population is unlikely and they may generally be defeated with efficient prophylaxis and treatment. Considering the study results -by Garus-Pakowska cited above -on compliance with hand hygiene of medical staff in dealing with patients, and another one taking into account the correct use of protective gloves (personal protective equipment) [6][7][8], or other authors [20,21] it may be stated that hospital staff often disregard the procedures aimed at protecting against harmful biological agents. Consequently, the hospital environment is not a safe work environment, and in particular it is not a microbiologically safe environment for patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Różańska et al [6] conducted among 414 medical students, only 53% of them knew the HH guidelines. In-depth knowledge of the WHO's "five moments for hand hygiene" among doctors and nurses seems to be a key issue in applying these guidelines in practice and, consequently, to reducing the number of nosocomial infections.…”
Section: Resultsmentioning
confidence: 99%
“…In-depth knowledge of the WHO's "five moments for hand hygiene" among doctors and nurses seems to be a key issue in applying these guidelines in practice and, consequently, to reducing the number of nosocomial infections. However, as research in Poland shows, poor knowledge of these principles can already be traced to medical students who did not internalise these principles prior to their first contact with the patient [6,10]. In a study by Wałaszek et al [10], in which 100 respondents (medical students, interns, physicians) were examined, it was found that 3/4 of the respondents did not correctly apply HH techniques and that compliance with HH principles was insufficient in all the "five moments for hand hygiene" (the highest score was 74%: before clean/aseptic procedures, and the lowest was 1%: after touching the patient's surroundings).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations